Evaluation of the effect of morphological control of dimorphic Mucor circinelloides on heterologous enzyme production - Sindle, Astrid Elizabeth (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Process Engineering))--University of Stellenbosch, 2006.